nm23, TOP2A and VEGF expression: Potential prognostic biologic factors in peripheral T-cell lymphoma, not otherwise specified - Huang, Wenting (Oncol Lett, 2019)
Peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) is an aggressive lymphoma associated with a poor outcome. To date, the factor consistently associated with prognosis is the International Prognostic Index (IPI) score; however, it is considered that the IPI score cannot be beneficial for guiding potential targeted therapies. New scoring systems have recently been developed. The aim of the present study was to observe the expression of NME/NM23 nucleoside diphosphate kinase 1 (nm23), nuclear DNA topoisomerase 2-α (TOP2A), multiple myeloma oncogene-1 (MUM-1) and vascular endothelial growth factor (VEGF), and evaluate their prognostic value in PTCL-NOS. A retrospective analysis of 124 cases of PTCL-NOS showed that 70/122 (57.4%) cases were positive for nm23, 71/122 (58.2%) for TOP2A, 30/119 (25.2%) for MUM-1 and 64/122 (52.5%) for VEGF. Of note, 50/122 cases concurrently expressed nm23, TOP2A and VEGF. The univariate analysis results revealed that the nm23 (P=0.012), TOP2A (P=0.002) and VEGF (P=0.008) expression had a negative prognostic effect in patients with PTCL-NOS, while the MUM-1 expression did not have a significant prognostic value (P=0.918). In addition, the concurrent expression of nm23, TOP2A and VEGF was significantly associated with a worse prognosis (P=0.002). However, in multivariate Cox regression analysis, the concurrent expression of nm23, TOP2A and VEGF tended to predict a worse prognosis, however the P-value was borderline (hazard ratio, 1.495; 95% confidence interval, 0.993–2.250; P=0.054). It is speculated that there may be an association among the expression of nm23, TOP2A and VEGF, and that their expression may serve as a promising prognostic factor for PTCL-NOS.